Food Cold Chain in Indonesia during the Covid-19 Pandemic: A Current Situation and Mitigation - Ilyas Masudin; Nika Tampi Safitri (Jurnal Rekayasa Sistem Industri, 2020)
The spread of the corona virus (COVID-19) has had a massive impact on all business sectors in Indonesia. Food cold supply chain is a business sector that is quite badly affected. This is because the food cold chain requires special treatment to maintain its quality, has a relatively short life and cannot be returned. This article discusses the impact of the COVID-19 pandemic and its social impacts such as social restrictions and area lockdown on the business of food cold chain. It also discusses mitigation that needs to be done to anticipate related issues such as food supply-demand, food safety and some transportation challenges